2008
DOI: 10.1108/00400910810874026
|View full text |Cite
|
Sign up to set email alerts
|

Contradictions in the practices of training for and assessment of competency

Abstract: PurposeThe purpose of this paper is to highlight the contradictions in the current maritime education and training system (MET), which is based on competency‐based education, training and assessment, and to theorize the failure to make the training useful.Design/methodology/approachA case study of education and training in the international maritime domain was conducted. Data sources include historical documents, rules and regulations concerning MET, syllabi, handouts, sample questions, field notes, an ethnogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 7 publications
0
43
0
1
Order By: Relevance
“…This is not unlike what we observe in other programs -such as the mariners we studied returning to upgrade their certificates (Emad & Roth, 2008). Here, too, both students and instructors knew that the course contents were irrelevant to the worksite, but both parties colluded so that students were properly prepared -in contrast with being more proficient on the worksite -to succeed in formal examinations on the basis of which they would receive their certificates.…”
Section: Electrical Apprentices Between College and Workplacementioning
confidence: 63%
See 1 more Smart Citation
“…This is not unlike what we observe in other programs -such as the mariners we studied returning to upgrade their certificates (Emad & Roth, 2008). Here, too, both students and instructors knew that the course contents were irrelevant to the worksite, but both parties colluded so that students were properly prepared -in contrast with being more proficient on the worksite -to succeed in formal examinations on the basis of which they would receive their certificates.…”
Section: Electrical Apprentices Between College and Workplacementioning
confidence: 63%
“…Much as in the fish hatcheries and mariner training programs we studied (Emad & Roth, 2008;Lee & Roth, 2004), the difference between college and work has its own discourse that allows the interaction participants to draw on the difference as a resource or topic. There are frequent articulations of differences between college and workplace methods, such as when journeymen and more senior apprentices point out, in the context of a specific job, how something would be taught in college and how things have to be done "in the real world" and "on the job.…”
Section: Electrical Apprentices Between College and Workplacementioning
confidence: 99%
“…Hontvedt (2015a) argues that training sessions have to be carefully configured in order for such pitfalls to be avoided. Studies examining the use of simulators in maritime training are actually direct warnings about simulator-based training and assessment as being poorly implemented in the MET system (Emad and Roth 2008;Sampson et al 2011). The problems reported concern both simulator misuse and lack of knowledge concerning how to provide efficient training and valid assessment in simulators.…”
Section: Introductionmentioning
confidence: 99%
“…McCallum and Smith (2000) evaluated simulators and provided a framework for their assessment. From another perspective, Cross (2003Cross ( , 2007, Emad and Roth (2008) researched the development of competence-based training and assessment in simulators. Other researchers have shown that training programs display some weaknesses in the development of decision making skills, when addressing the management of complex situations (Chauvin, Clostermann, & Hoc, 2009).…”
Section: Navsim Training and Educationmentioning
confidence: 99%